2017
DOI: 10.1093/annonc/mdx416
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived xenografts effectively capture responses to oncology therapy in a heterogeneous cohort of patients with solid tumors

Abstract: Integration of PDX models as a preclinical platform for assessment of drug efficacy may allow a higher success-rate in critical end points of clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
237
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(246 citation statements)
references
References 34 publications
3
237
1
5
Order By: Relevance
“…There is a need for preclinical models that faithfully represent this heterogeneity. Patient‐derived xenografts (PDXs) models are robust preclinical models to test targeted therapies because they conserve each patient's molecular heterogeneity and response to treatment . These models have emerged as an important translational research tool to identify new treatments and predictive biomarkers .…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for preclinical models that faithfully represent this heterogeneity. Patient‐derived xenografts (PDXs) models are robust preclinical models to test targeted therapies because they conserve each patient's molecular heterogeneity and response to treatment . These models have emerged as an important translational research tool to identify new treatments and predictive biomarkers .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that PDXs retain the genome-wide exomic nucleotide variants, gene copy number alterations, and DNA methylation patterns of their corresponding tumors [1][2][3][4] irrespective of the number of passages, 1,3 although clonal selection during initial engraftment and passaging of PDXs has been observed. They have been shown to recapitulate the histologic and genetic features of human primary tumors and to be useful in assessing treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that PDXs retain the genome-wide exomic nucleotide variants, gene copy number alterations, and DNA methylation patterns of their corresponding tumors [1][2][3][4] irrespective of the number of passages, 1,3 although clonal selection during initial engraftment and passaging of PDXs has been observed. 4 PDX models also are increasingly used in the mechanistic characterization of resistance to targeted therapies, [9][10][11] the identification of novel Cancer November 1, 2019 biomarkers 12 and therapeutic targets, 13 and the characterization of intratumoral heterogeneity. 7,8 An analysis of the treatment responses of PDXs established from 92 patients with different solid tumors demonstrated a significant association between drug response in patients and the response in mice bearing the corresponding PDXs, indicating that PDXs can predict clinical treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with those of Izumchenko et al. that PDXs can more accurately replicate patient outcomes, supporting the capacity of these models to correctly guide treatment decisions that are most likely to be beneficial clinically …”
Section: Discussionmentioning
confidence: 99%